Delivery of microRNA-302a-3p by APTES modified hydroxyapatite nanoparticles to promote osteogenic differentiation in vitro - Pirawish Limlawan; Laurine Marger; Stéphane Durual; Anjalee Vacharaksa (Nature Publishing Group, 2023)
Abstract Objective To demonstrate the miRNA delivery by hydroxyapatite nanoparticles modified with APTES (HA-NPs-APTES) and promote osteogenic gene expression. Materials and methods Osteosarcoma cells (HOS, MG-63) and primary human mandibular osteoblasts (HmOBs) were co-cultured with HA-NPs-APTES conjugated with miRNA-302a-3p. Resazurin reduction assay was performed to evaluate HA-NPs-APTES biocompatibility. Intracellular uptake was demonstrated by confocal fluorescent and scanning electron microscopy. The miRNA-302a-3p and its mRNA targets expression levels including COUP-TFII and other osteogenic genes were assessed by qPCR on day1 or day5 post-delivery. Calcium deposition induced by the osteogenic gene upregulation was shown by alizarin red staining on day7 and 14 post-delivery. Results Proliferation of HOS cells treated with HA-NPs-APTES was similar to that of untreated cells. HA-NPs-APTES was visualized in cell cytoplasm within 24 hours. MiRNA-302a-3p level was upregulated in HOS, MG-63 and HmOBs as compared to untreated cells. As a result, COUP-TFII mRNA expression was reduced, followed by an increase of RUNX2 and other osteogenic genes mRNA expression. Calcium deposition induced by HA-NPs-APTES-miR-302a-3p in HmOBs was significantly higher than in untreated cells. Conclusion HA-NPs-APTES may support the delivery of miRNA-302a-3p into bone cells, as assessed by osteogenic gene expression and differentiation improvement once this combination is used on osteoblast cultures.